Frequency of Post Operative Complications of Mesh Repair in Patients with Paraumbilical Hernia - Zain Ihsan; Arif, Atta Ullah; Bano, Shaher; Ihsan, Aleeha; Ihsan ul Haq (Indus Journal of Bioscience Research, 2025)
Background: Paraumbilical hernia is a common ventral abdominal wall defect frequently managed by mesh repair to reduce recurrence rates. Despite its advantages, mesh implantation may predispose patients to early postoperative complications. This study aimed to determine the frequency of postoperative complications following mesh repair in patients with paraumbilical hernia. Methods: This is a cross-sectional descriptive study, which was carried out at the Department of Surgery, Lady Reading Hospital, Peshawar, between 2 December 2024 and 2 May 2025. One hundred and twenty patient’s anesthetics for elective open mesh repair were included in the study population based on non-probability sequential sampling between 18 and 65 years. Patients that were incarcerated or had their hernias strangled and those that were undergoing active infection were locked out. In all cases, polypropylene mesh was positioned in the sublay position. The 15 days evaluation period included the postoperative complications such as wound infection, seroma, and hematoma. The data were examined with SPSS version 21, and there was the stratification in order to detect relations to demographic and clinical variables. Results: The average age was 41.8 +11.6 years and 56.7% of the patients were females. The general incidence of postoperative complications was 17.5 percent. The most frequent complication was wound infection (8.3%), then seroma (5.8%) and hematoma (3.3%). Diabetes mellitus (p = 0.03) and smoking status (p = 0.04) had significant associations with complications whereas age, gender, BMI, and hypertension did not have significant association with complications. Conclusion: Mesh repair of paraumbilical hernia showed a satisfactory initial morbidity. Surgical outcomes can be further enhanced by optimization of modifiable risk factors like diabetes and smoking.